Analisis Wacana Kritis Komodifikasi DaÃ Dalam Program Televisi - Ridwan Rustandi (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2018)
This study aims to determine the construction of preachers in a television broadcast. The study was conducted to answer the question of how identity construction preachers and how preachers selection criteria in propaganda programs on television. The study was conducted with a qualitative approach and methods of Critical Discourse Analysis Teun Van Dijk Models. There are three element of Critical Discourse Analysis Methods : Text, Social Cognition and Social Context. Data collection techniques used in this study is the observation, interviews, and documentation. The results showed that the commodification of propaganda on the program